A REVIEW ON NANOEMULSIONS FOR OPHTHALMIC DRUG DELIVERY: ADVANCES AND FUTURE PERSPECTIVES - Sagnik Sarkar,; Ishita Ranjan,; Shahma Shirin,; Kundan Kumar,; Dr.H.Gayathri, (The Bioscan, 2026)
Nanoemulsions have emerged as a promising platform for ophthalmic drug delivery due to their ability to enhance drug solubility, stability, and bioavailability while ensuring patient compliance. This review provides a comprehensive overview of the formulation, advantages, challenges, and applications of nanoemulsions in ophthalmology. Recent advancements in nanoemulsion technology and their potential to overcome ocular barriers are highlighted, along with future directions in the field.